Modeling of Tectonic-Thermal Evolution of Cretaceous Qingshankou Shale in the Changling Sag, Southern Songliao Basin, NE China - Liu, Yuchen; Liu, Bo; Cheng, LiJuan; Xing, Jilin; Tian, Shansi; Huang, Saipeng; Dong, Suying (Frontiers in Earth Science, 2021)
Significant breakthroughs and discovery of shale oil have been made recently in the Upper Cretaceous Qingshankou Formation in the Songliao Basin, providing a new resource target for shale oil exploration of Northeast China. Understanding the tectonic-thermal evolution and maturation histories of Qingshankou Formation are significant aspects of shale oil exploration and evaluation. This study reconstructed the thermal history of Qingshankou Formation since the Late Cretaceous, the results show there are two phases of thermal evolution in the south part of Songliao Basin: (1) The gradual heating stage during the Late Cretaceous, the heat flow is gradually increasing during this period and reach the maximum heat flow value in the end of the Cretaceous; (2) The decline stage since Neogene, the tectonic activity is relatively stable and the geothermal heat flow is gradually reduced during this period, and the present-day heat flows range from 60.1 mW/m2 to 100.7 mW/m2, with an average of 78.2 mW/m2. In addition, the maturity histories of the organic-rich shale were reconstructed based on the new thermal histories. The Cretaceous Qingshankou shales underwent deep burial thermal metamorphism in the end of the late Cretaceous and uplift thermal fading since Neogene. Based on the maturity model, the hydrocarbon generation and expulsion since the Late Cretaceous period of K2qn1 were modeled. Overall, tectonic movement, which controls basin evolution, determines the intensity and timing of hydrocarbon generation and expulsion in the study area.